The Role of Financial Distress in Mediating The Accounting Conservatism Practices - Ratieh Widhiastuti; Selvia Rahayu (AKRUAL: JURNAL AKUNTANSI, 2022)
Conservatism is a prudent reaction to uncertain conditions aimed at protecting the rights and interests of shareholders, and lenders who determine higher standard verification to recognize good news rather than bad news. Several phenomena that indicate the lack of application of accounting conservatism are the many fraudulent acts of internal company parties. This study aimed to determine the effect of the board of directors, firm size, leverage on accounting conservatism through financial distress as a mediating variable. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The research sample was determined by purposive sampling method so that there were 174 analysis units. The data use published annual reports. The analysis tool used descriptive analysis and path analysis. The results showed that financial distress, firm size, and leverage had a significant positive, but the board of directors had no effect on accounting conservatism. The board of directors and leverage had a significant negative effect on financial distress. Firm size had a significant positive effect on financial distress. Financial distress significantly mediated the effect of firm size and leverage, but was unable to mediate the effect of the board of directors on accounting conservatism